Supplemental Material: Rhabdophane Th-Pb ages indicate reactivation of Mesoarchean structures in west Pilbara Craton during breakup of Greater India and Australia-Antarctica - Birger Rasmussen (8927246); (281964) (2021)
Analytical methods and results, Figure S1, and Tables S1–S3.